Law and technology - Mokhtar, Khairil Azmin (2018)
Law is a dynamic concept, which keeps on changing with time and place. It must change with changes in the society. Each year brings a fresh crop of scientific discoveries. Knowledge that was accumulated a decade ago becomes out of date. Fresh fields are trodden, fresh avenues explored, fresh phenomena unearthed every year. These discoveries and explorations increase not only in quantity and number; they touch individual and social life at so many points. These are the points that ultimately become the points of contact between science and the law. It is in this manner that scientific developments result in an increase in the need of legal response to the various points of contact. It is a legitimate task of the law to consider the social merits and demerits of scientific or other development and regulate human conduct. It is the task of the law to guide and shape the world, and to deal with the dynamics of science, technology and technical developments and their effect on human beings. If science is the father of truth, then surely law must be its mother, ready to be impregnated with the vital germ, to nourish the embryo and bring it to birth. Social evolution, and biological and technological progress, must, of necessity, be accompanied by changes in law; changes in the sense of modernization and reform. The interaction and collaboration between law on one hand, and science and technology, on the other today is a must. This paper seeks to dtermine the interelation between law and science.